1996
DOI: 10.3109/10409239609108722
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry and Biology of DNA Methyltransferases

Abstract: Recognition of a specific DNA sequence by a protein is probably the best example of macromolecular interactions leading to various events. It is a prerequisite to understanding the basis of protein-DNA interactions to obtain a better insight into fundamental processes such as transcription, replication, repair, and recombination. DNA methyltransferases with varying sequence specificities provide an excellent model system for understanding the molecular mechanism of specific DNA recognition. Sequence comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
45
0
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 107 publications
0
45
0
2
Order By: Relevance
“…DNA methyltransferases (MTases) 1 are involved in a variety of important cellular functions in both prokaryotes and eukaryotes (1)(2)(3). In addition, DNA MTases are excellent subjects for detailed studies of specific protein-DNA interaction because they are highly specific and have a comparatively simple organization.…”
mentioning
confidence: 99%
“…DNA methyltransferases (MTases) 1 are involved in a variety of important cellular functions in both prokaryotes and eukaryotes (1)(2)(3). In addition, DNA MTases are excellent subjects for detailed studies of specific protein-DNA interaction because they are highly specific and have a comparatively simple organization.…”
mentioning
confidence: 99%
“…Methyltransferase-catalyzed modification of substrate DNA, RNA, or protein serves as a key signal in the regulation and maintenance of diverse biological processes in a range of organisms from prokaryotes to eukaryotes (1,2). Subsequent to its isolation from Hemophilus haemolyticus nearly a quarter century ago, HhaI DNA methyltransferase (M.HhaI) 1 has been subjected to incisive investigations yielding detailed insights into the reaction chemistry (3)(4)(5)(6)(7).…”
mentioning
confidence: 99%
“…For example, it was recently shown that an active dam gene is crucial for the manifestation of pathogenic properties of Salmonella typhimurium, as well as a number of other bacteria that inhabit the human intestine (3). The biological role of other prokaryotic MTases, which mainly belong to the type II class of modification enzymes, appears to be limited to the protection of cellular DNA against hydrolysis by their cognate restriction endonucleases (1), although their wider biological participation in cellular metabolism is under discussion (4). Thus, the elucidation of the mechanism of action of DNA MTases is of great interest.…”
mentioning
confidence: 99%